Familial ties and citizen claims: photography and early civil rights activism in African–Canadian newspapers. Issue 4 (20th October 2021) - Moser, Gabrielle
Abstract : This paper examines the visual cultures of early civil rights activism in Canada in the period following the enactment of the country's first citizenship laws in 1947. It does so through a close study of the use of family photographs in The Clarion (1946–49), an African-Canadian–owned Atlantic newspaper which regularly reprinted family photographs on its front cover and within its pages, alongside reports on racial discrimination, calls for political activism and celebrations of the achievements of Black Canadians. Paying particular attention to The Clarion's reporting on the arrest of Viola Desmond – a local beautician who publicly challenged segregation laws in a Nova Scotia movie theatre in 1946 – the essay charts how these domestic and private images prefigured now well-established debates about respectability politics and quietness in civil rights discourse and image making on both sides of the border. It seeks not to resolve these tensions but to demonstrate the uneasy ways questions of self presentation have informed the imagery of citizen claims by racialised subjects in North America in the post-war period.